Estrategias didácticas para la enseñanza de fenómenos luminosos en bachillerato general unificado - Arias Ortega, Cristian Alexander (2025)
Didactic strategies contribute to the development of meaningful learning and serve as procedures correctly oriented to the consolidation of knowledge and skills. This research analyzed the didactic strategies implemented in the teaching-learning process of luminous phenomena. The approach followed by the research is mixed, with documentary and field design, with descriptive scope. For the collection of information, the techniques used were documentary review, file recording and the elaboration of surveys; while the instruments, included a search log, content cards, a questionnaire addressed to students and a semi-structured interview with teachers. The sample was composed of 58 students in the third year of high school and 3 teachers of the “Unidad Educativa Fiscomisional Daniel Álvarez Burneo”. The results obtained determined that teachers mainly use summaries and intended questions, which suggests the necessity of diversifying and strengthening the educational process through the implementation of other types of strategies, avoiding the conventional conceptions of the present time